مستوى أداء مستشاري التوجيه المدرسي و المهني من وجهة نظر مديري المؤسسات التربوية دراسة ميدانية بمدينتي البيض و الأغواط - حساني حدة; بن يطو ندى اسمهان; ملياني عبد الكريم (My University, 2018)
The study aimed at revealing the level of guidance and vocational guidance directed to secondary school students from the point of view of managers of secondary and intermediate educational institutions in the governorates of elbayadh and Laghouat. Based on the analytical descriptive approach, the number of sample members reached (60) managers . The questionnaire of guidance and vocational guidance was prepared by the two students. The social package (SPSS) was used for statistical processing, after data was developed and unloaded The study found the following results: The level of performance of guidance and guidance counselors for the extension process is average. There were no statistically significant differences in the level of performance of guidance and guidance counselors due to the gender variable. There were no statistically significant differences in the level of performance of guidance and guidance counselors due to the years of seniority. There were no statistically significant differences in the performance level of the guidance consultants due to the different type of training.